CDK14 expression is down-regulated by cigarette smoke in vivo and in vitro. Issue 2 (16th April 2015) - Pollack, Daniel; Xiao, Yuxuan; Shrivasatava, Vibha; Levy, Avi; Andrusier, Miriam; D'Armiento, Jeanine; Holz, Marina K.; Vigodner, Margarita
Abstract In this study, DNA arrays have been employed to monitor gene expression patterns in testis of mice exposed to tobacco smoke for 24 weeks and compared to control animals. The results of the analysis revealed significant changes in expression of several genes that may have a role in spermatogenesis. Cdk14 was chosen for further characterization because of a suggested role in the testis and in regulation of Wnt signaling. RT-PCR analysis confirmed down regulation of Cdk14 in mice exposed to cigarette smoke (CS). Cdk14 is expressed in all testicular cells; spermatogonia- and Sertoli-derived cell lines treated with cigarette smoke extract (CSE) in vitro showed down-regulation of CDK14 mRNA and protein levels as well as down-regulation of β-catenin levels. CS-induced down-regulation of CDK14 mRNA and protein levels was also observed in several lung epithelium-derived cell lines including primary normal human bronchial epithelial cells (NHBE), suggesting that the effect is not restricted to the testis. Similar to testicular cells, CS-induced down-regulation of CDK14 in lung cells correlated with decreased levels of β-catenin, a finding suggesting impaired Wnt signaling. In the lungs, CDK14 was localized to the alveolar and bronchial epithelium.